The reduction of working hours from Marxist theory: An analysis of the EU - Briñas Barba, Álvaro (Papeles de Europa, 2020)
Since the emergence of capitalism, increases in productivity have allowed workers to produce the same amount of goods in increasingly shorter amounts of time. However, during the 20th century and the 21st century, this had no effect on the number of hours spent working by employees, which has remained the same since the introduction of the 8 hour working day in the 19th century. Increasing productivity could have led to a reduction in the working day, resulting in employees having more spare time. Nevertheless, this did not happen due to the upper class taking hold of the majority of the profits resulting from productivity.In this dissertation, the consequences of the increase in productivity on the upper and working class, as well as the effects that a reduction in working hours could have on both classes will be analysed  using the Marxist theory. In order to support this with evidence, the performance of five economies in the European Union will be analysed, along with the effects a reduction in the working day could have on them.
Keywords: working hours; productivity; reduction in the working day; relative surplus; workforce; relative income